INTANGIBLE ASSETS IMPAIRMENT TEST ISSUES: THE CASE OF A BRAZILIAN TELECOMMUNICATIONS COMPANY - Lustosa, Paulo Roberto Barbosa; Rodrigues, Fernanda Fernandes; Gonçalves, Rodrigo de Souza; Vieira, Leonardo (Advances in Scientific and Applied Accounting, 2011)
National and international regulatory agencies by issuing new standards have tried to bring the accounting recorded values near to economic values. Nevertheless, it is understood that the latter carry a deeper level of subjectivity, on the grounds that completely new values will be obtained by the adoption of different conditions. This study aims to perform a comparative analysis between two company valuation methods: the Discounted Cash Flow and the Residual Income Valuation while performing the impairment test. The study case uses the database prepared by a telecommunications company to its subsidiary in the Internet sector for the purpose of the impairment test assessment. Some points have been identified as deserving special attention in a company’s valuation assessment, namely the discount rate and the growth rate. The results show that: 1) a firm’s economic value is sensitive to the use of a sole growth rate to calculate the perpetuity, considering that any changes in the rate will alter the decision based on the test; 2) the setup of a discount rate as a parameter in a firm’s valuation assessment is a fundamental point for the write-off decision resulting from an impairment test.